Potential plant traits and mechanisms behind methane emissions in rice and target genes for further dissection of their roles - Roy, Ripon Kumar; Hosseiniyan Khatibi, Seyed Mahdi; Trijatmiko, Kurniawan Rudi; Diaz, Maria Genaleen Q.; Ocampo, Eureka Teresa M.; Hernandez, Jose E.; Henry, Amelia; Kohli, Ajay (Taylor & Francis, 2025)
Rice fields are among the leading global agricultural sources of anthropogenic methane emissions,with the rice plant tissue playing a central role in the generation of methane (CH4) and the emissionprocess. Due to the variability of methane emissions trends across studies, contrasting rice plant traitsand mechanisms have often been reported to affect methane emissions. Here, we review thereported traits and mechanisms together with genes that have been identified as being associatedwith those traits, as a resource for future research using genome editing to pinpoint the factorsaffecting methane emissions in rice. Methane production in flooded soils involves several interactingagents, with the rice plant supplying root exudates to methanogenic archaea and facilitatingmethane transport from soil to the atmosphere through aerenchyma. Conversely, the same aerench-yma system transports atmospheric oxygen to the roots; this oxygenation of the rhizospheresupports methanotrophs which consume methane, thus mitigating emissions. Varietal differencesin traits such as barriers to radial oxygen loss, root exudates, root architecture, and growth duration,have also been reported to influence methane production and emissions. Previous studies weretypically conducted on lines with large differences in the genetic backgrounds; comparisons ofmethane emissions between lines with very similar backgrounds, for example as developed throughgenome editing, might help better define the effects of these traits. The genes highlighted in thisreview are linked to the traits and mechanisms potentially affecting methane emissions in rice andcould be targeted for genome editing and subsequent comparison of methane emissions.